Factors Responsible For The Spread of Islamic Societies In Yorubaland - O. R. Azeez; Zakariyah, Abdulganiyi Abinbade Zakariyah (Maklumat: Journal of Da'wah and Islamic Studies, 2025)
Islamic societies spread out in the Yorubaland with some factors, causes and reasons that led to their spread, and these factors are aiming to examine and discuss in this paper. This paper intend to use the historical method, in which the researcher follows the history of each society, to realize the reasons that led to its establishment, therefore the researcher divides his work into several factors, including: religious, social, moral, cultural factors and many others. The researcher explains each factor separately to make it easier for the reader to understand each of them fully, and the researcher extracts from the study of these factors that each of these societies claims that the reason for their establishment is to spread and teach Islam, the researcher recommends in conclusion that all these societies should adhere to the Qur'an, Sunnah and sound belief in carrying out the activities in their society, and avoid fanaticism and partisanship, and to see other societies as their brothers, but the difference in names and not in belief and principle, and to deal with each other with love and familiarity, so that their followers should emulate good character from them.